(untitled) (Research, Society and Development, 2022)
The present investigation started from the question: Can teacher training for the use of the WebQuest tool contribute to the development of research as a pedagogical principle in the scope of Vocational and Technological Education? The studies developed aim to collaborate in the deepening of teachers’ knowledge about the epistemological, didactic and operational principles of the WebQuest tool, in order to favor the orientation of school research in virtual sources, during classroom teaching or remote. The research is qualitative in nature and serves exploratory and descriptive purposes. The action research method was adopted, considering its suitability for solving problems that are of interest to the researcher and the research participants. The historical-dialectical materialist conception enabled the perception and critical analysis of the reality experienced during the diagnostic phase (2019) and the period of application of the Didactic Sequence (2021), marked by a pandemic. The results of this investigation were analyzed following the path of hermeneutic-dialectical thinking and demonstrate that the WebQuest tool favors the inseparability of teaching and research; in the Remote Learning context, it is an effective tool in the process of guiding asynchronous activities. The biggest challenge identified for the use of WebQuest is the methodological construction of a proposal in which students and educators act as producers of knowledge, and not just as subjects who follow scripts or indicate sources of information for the research. Overcoming this challenge requires investment in teacher training, as well as guaranteeing time so that teachers can act as researchers and producers of didactic tools.